Rapid sol–gel synthesis of honeycomb-layered Na3Ni2BiO6 and orthorhombic Na3Ca2BiO6. Issue 10 (16th February 2023) - Luke, Emily J.; Potticary, Jason; Friedemann, Sven; Hall, Simon R.
Abstract : We present a new synthesis of a material that could have potential as a cathode material for sodium-ion batteries, Na3 Ni2 BiO6 . We also apply this synthesis to a relatively unexplored material, Na3 Ca2 BiO6 and investigate its magnetic properties. Abstract : The A3 M2 M′O6 type materials Na3 Ca2 BiO6 and Na3 Ni2 BiO6 were successfully synthesised through two sol–gel techniques – a method based on a natural deep eutectic solvent, and a biopolymer-mediated synthesis. The materials were analysed using Scanning Electron Microscopy to determine if there was a difference in final morphology between the two methods, and it was found that the natural deep eutectic solvent method resulted in a more porous morphology. For both materials, the optimum dwell temperature was found to be 800 °C, which in the case of Na3 Ca2 BiO6 was a much less energy-intensive synthesis process than its seminal solid-state synthesis. Magnetic susceptibility measurements were undertaken on both materials. It was found that Na3 Ca2 BiO6 exhibits only weak, temperature independent paramagnetism. Na3 Ni2 BiO6 was found to be antiferromagnetic, with a Néel temperature of 12 K, in line with previously reported results.